Yvan Goll – Ε. Χ. Γονατάς: Προς μια συγκριτική ποιητική - Γαλανάκης, Αθανάσιος Β. (Σύγκριση/Comparaison/Comparison, 2018)
This study aims to explore the relationship between the works of Yvan Goll and E. Ch. Gonatas. More specifically, the main purpose of the study is to highlight the role played by the Expressionist Movement (in which Yvan Goll was an active member) in the literary works of E. Ch. Gonatas. The methodological tools of Comparative Literature and Hermeneutics are used to prove the close relationship between the two authors and the expressionistic texture of their art. In the first part, the study is concerned with the expressionistic imagery, the poetics of landscape, the use of colors and the symbolization of nature (especially through the motif of the humanization of animals). The second part deals with the influence of Expressionism on the mutability of the literary genres, the generic hybridization in the work of E. Ch. Gonatas and the small literary form. The main objectives of the study are: i) A heuristic report of the presence of Expressionism in Modern Greek Literature (especially in the post-surrealistic movement), ii) the clarification of certain aspects in Gonatas' poetics and iii) the acquaintance with the work of the major poet but unknown to the Greek general public, Yvan Goll.